Assessment of Knowledge, Attitude and Practices towards Gender Equality in Achieving SDG5 - Maliha Jahan, (Pusbindiklatren Bappenas, 2021)
This research was conducted to determine the awareness level of the students’ at the Universityof Malaya (UM) towards gender equality in achieving SDG5. A set of survey questionnaire established onKnowledge, Attitude, and Practices (KAP) was distributed through an online Google survey form to allUM students’, and 123 responses were collected to evaluate the awareness level (95% confidenceinterval with ± 5% margin of error). Data analysis was conducted through SPSS software. The resultsrevealed that the respondents have a higher knowledge level with lower attitude and practices levels.Spearman’s Rho coefficient correlation was used to evaluate the relationship level within variables(between knowledge and practices and attitude and practices). The results reported a weak positivecorrelation within knowledge and practice levels (r= .275, N= 123, p=